2012
DOI: 10.1134/s1061934812070040
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel analyzers of atomic emission spectra: Current state and analytical potentials

Abstract: The structure and characteristics of a modern tool for recording and processing emission spectra, that is, multichannel analyzer of atomic emission spectra (MAES), based on multicrystal assemblies of pho todiode arrays, as well as spectral parameters of the instruments equipped with these analyzers are presented. The analytical potentials of MAES spectrometers are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…A microwave ion source has been adapted for AMS 98 Labusov et al 102 presented an overview of the current status of multichannel analysers used in AES, specifically multicrystal assemblies of photodiode arrays. Hadjar et al 103 have reported some performance data for an IonCCD detector developed for a Mattauch-Herzog miniature MS.…”
Section: Secondary Ion Massmentioning
confidence: 99%
“…A microwave ion source has been adapted for AMS 98 Labusov et al 102 presented an overview of the current status of multichannel analysers used in AES, specifically multicrystal assemblies of photodiode arrays. Hadjar et al 103 have reported some performance data for an IonCCD detector developed for a Mattauch-Herzog miniature MS.…”
Section: Secondary Ion Massmentioning
confidence: 99%
“…Элементүүдийн агуулгыг тодорхойлох Pb, Zn, Cd, Mn, Co, Ni, Cr ба Cu -ийн нийт агуулгыг олон сувагт атомын цацаргалтын спектроскопийн нуман атомчлалын хуурай дээжийг нүүрсэн электродын дундуур үлээлгэн атомчлах аргаар тодорхойлсон [21,22 ]. Хөрсөн дэх хүнд элементийн бохирдлын түвшин Улаанбаатар хотын өнгөн хөрсөн дэх хүнд элементийн бохирдлын түвшин, хөрсөн дэх хүнд элементүүдийн бохирдлын хүрээлэн буй орчинд үзүүлэх сөрөг нөлөө, бохирдлын эх үүсвэрийн ялгааг олон улсад хөрсний экологийн ба геохимийн үнэлгээ хийхэд хамгийн түгээмэл хэрэглэдэг бохирдлын индекс (PI), баяжилтын фактор (EF) ба сөрөг нөлөө буюу эрсдлийн фактор (E r ) гэсэн нэг элементийн индексүүдээр үнэлсэн [23][24][25][26][27][28].…”
Section: материал аргазүйunclassified
“…Labusov et al 102 presented an overview of the current status of multichannel analysers used in AES, specically multicrystal assemblies of photodiode arrays. Hadjar et al 103 have reported some performance data for an IonCCD detector developed for a Mattauch-Herzog miniature MS.…”
Section: Instrumentationmentioning
confidence: 99%